McLuhan, M. ve Fiore, Q. (2012). Medya mesajı, medya masajıdır: McLuhan'ın izinde medyayı anlama kılavuzu. (İ. Haydaroğlu, Çev.). J. Agel (Yay. Haz.). İstanbul: MediaCat. - (:unkn) unknown (My University, 2014)
0
Keywords: Bilgi, Belge Yönetimi